Ultrasonic assisted pulse electrodeposited Ni-doped TiN coatings. Issue 12 (15th August 2018) - Cui, Wei; Zhang, Yuhang; Song, Rixuan; Wang, Peter
Abstract: Ni-doped TiN coatings were deposited on 45 steel surfaces by ultrasound assisted pulse electrodeposition (UAPE) from reformative Watt nickel-based electrolytes. The effects of ultrasonic intensities on microstructure, chemical composition, nanomechanical and corrosion properties of the obtained coatings were investigated by X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), nanoindenter, and electrochemistry. Ni-doped TiN coatings deposited at 20 W/cm 2 showed fine and compact morphologies, with large amounts of TiN particles evenly embedded in the coatings. The average atomic percents of Ti and N elements in the coatings were estimated to approximately 17.3 at% and 24.8 at%, respectively. In addition, the Ni-doped TiN coating produced at 20 W/cm 2 revealed fine, uniform, and exiguous structures in the micro areas. The average diameters of TiN nanoparticles and Ni grains were estimated to around 32.3 nm and 71.8 nm, respectively. The maximum Young's modulus and microhardness values of Ni-doped TiN coatings produced at 20 W/cm 2 were measured as 167.8 and 34.3 GPa, respectively. Also, the Ni-doped TiN coating obtained at 20 W/cm 2 presented the highest R t and lowest C d values, indicating superior corrosion resistance and smooth surface coating.